Analysis of Inclusive Economic Development of Environmental Quality in Indonesia by Examining Environmental Kuznets Curve - Suharto, Rahcmad Budi; Rochaida, Eny; Roy, Juliansyah; Permana, Meiki (International Journal of Energy Economics and Policy, 2021)
This study analyzes the relationship of inclusive economic development to the quality of the environment in Indonesia. Secondary data used was derived from Bappenas, Ministry of Environment and Forestry of the Republic of Indonesia, period from 2013 to 2017. The results showed that inclusive economic development still resulted in environmental degradation. The inclusive economic development index, which is one of the sustainable development goals that represent the achievement of economic dimensions and social dimensions, leads to degradation of the environmental extent. The Environmental Kuznets Curve (EKC) did not occur in the year of observation of this study. The recommendation for stakeholders is to prioritize environmental sustainability in every policy taken. For future researchers may consider research to determine indicators of sustainable development, which are composite indicators consisting of all dimensions (economic, social, environmental). Keywords: inclusive economic development; sustainable environmental quality; Sustainable development. JEL Classifications: O10, Q56 DOI: https://doi.org/10.32479/ijeep.11114